Promoting Energy Transfer via Manipulation of Crystallization Kinetics of Quasi‐2D Perovskites for Efficient Green Light‐Emitting Diodes. Issue 40 (15th August 2021) - Guo, Zhenyu; Zhang, Yu; Wang, Bingzhe; Wang, Liding; Zhou, Ning; Qiu, Zhiwen; Li, Nengxu; Chen, Yihua; Zhu, Cheng; Xie, Haipeng; Song, Tinglu; Song, Lei; et al.
Abstract: Quasi‐2D (Q‐2D) perovskites are promising materials applied in light‐emitting diodes (LEDs) due to their high exciton binding energy and quantum confinement effects. However, Q‐2D perovskites feature a multiphase structure with abundant grain boundaries and interfaces, leading to nonradiative loss during the energy‐transfer process. Here, a more efficient energy transfer in Q‐2D perovskites is achieved by manipulating the crystallization kinetics of different‐ n phases. A series of alkali‐metal bromides is utilized to manipulate the nucleation and growth of Q‐2D perovskites, which is likely associated with the Coulomb interaction between alkali‐metal ions and the negatively charged PbBr6 4– frames. The incorporation of K + is found to restrict the nucleation of high‐ n phases and allows the subsequent growth of low‐ n phases, contributing to a spatially more homogeneous distribution of different‐ n phases and promoted energy transfer. As a result, highly efficient green Q‐2D perovskites LEDs with a champion EQE of 18.15% and a maximum brightness of 25 800 cd m –2 are achieved. The findings affirm a novel method to optimize the performance of Q‐2D perovskite LEDs. Abstract : A homogeneous distribution of different‐ n phases and more efficient energy transfer is realized in quasi‐2D perovskites. The origin is found to be the manipulation of the crystallization kinetics, where the addition of potassium restricts the nucleation of high‐ n phases and allows the growth of low‐ n phases, resulting in an external quantum efficiency of 18.15%.